Disoriented : Asian Americans, law, and the nation-state - Chang, Robert S. (Critical America., 1999)
Does ""Asian American"" denote an ethnic or racial identification? Is a person of mixed ancestry, the child of Euro- and Asian American parents, Asian American? What does it mean to refer to first generation Hmong refugees and fifth generation Chinese Americans both as Asian American?. In Disoriented: Asian Americans, Law, and the Nation State, Robert Chang examines the current discourse on race and law and the implications of postmodern theory and affirmative action-all of which have largely excluded Asian Americans-in order to develop a theory of critical Asian American legal studies. Demon